1993
DOI: 10.1080/02701367.1993.10608817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Same-Sex versus Coeducational Physical Education on the Self-Perceptions of Middle and High School Students

Abstract: The purpose of this field experiment was to investigate the effects of attending either a coeducational or a same-sex physical education class on several self-perception variables. Middle and high school youth who had previously been in coeducational classes were assigned to either a same-sex or a new coeducational physical education class for a 10-lesson unit of basketball. Analyses were conducted at both the group and the individual levels. Self-perception variables examined included perceived self-confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
14

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 19 publications
2
18
0
14
Order By: Relevance
“…Current results suggest that girls-only classes can provide more emphasis on building the motor and sports skills many girls lack. Findings from previous studies indicate many girls do not prefer coeducational physical education classes (Lirgg, 1993(Lirgg, , 1994Treanor et al, 1998) and suggest they may be disadvantaged during them. Thus, some educational needs of adolescent girls might be better addressed in girls-only physical education.…”
Section: Test Of Mediation Lesson Contextmentioning
confidence: 95%
See 1 more Smart Citation
“…Current results suggest that girls-only classes can provide more emphasis on building the motor and sports skills many girls lack. Findings from previous studies indicate many girls do not prefer coeducational physical education classes (Lirgg, 1993(Lirgg, , 1994Treanor et al, 1998) and suggest they may be disadvantaged during them. Thus, some educational needs of adolescent girls might be better addressed in girls-only physical education.…”
Section: Test Of Mediation Lesson Contextmentioning
confidence: 95%
“…Nonetheless, male and female students received differential treatment in coeducational physical education decades ago (Dunbar & O'Sullivan, 1986, O'Sullivan, Bush, & Gehring, 2002, and several authors raised doubts about the adequacy ofgirls' participation in these settings (Treanor, Graber, Housner, & Wiegand, 1998;Turvey & Laws, 1988;Wolf et al, 1993). 446 Treanor et al (1998) and Lirgg (1993Lirgg ( , 1994 found both boys and girls preferred single-gendered physical education formats, but other studies countered this notion (Griffin, 1984(Griffin, , 1985. Meanwhile, Griffin (1984) found that coeducational physical education was not negative for all girls or positive for all boys.…”
mentioning
confidence: 94%
“…This finding is coherent with studies that have demonstrated how gender determines children's perception within physical education classes and how it affects task engagement. Specifically, research that has examined the treatment of children of different genders has demonstrated that girls receive less positive feedback and do not have the same chances to participate as boys [49]. Teachers generally pay more attention to boys than girls and, as research shows, it is likely that children are aware of this unequal treatment and that it affects their perception and behaviour [50].…”
Section: Discussionmentioning
confidence: 99%
“…Así, las clases coeducacionales y las clases de igual sexo han sido comparadas en función del rendimiento de sus alumnos mediante tests de habilidad o tests de logro. La mayoría de estudios han encontrado diferencias mínimas o ninguna en el rendimiento de los alumnos en clases tanto coeducacionales como de igualdad de sexo (Brightwell, 1969;Tallman, 1970), debido, en cierta manera, al hecho de que pocas diferencias en el rendimiento pueden ser demostradas en periodos cortos en el tratamiento de dos o tres semanas de instrucción (Lirgg, 1993).…”
Section: Estudios Sobre Discriminación Del Sexo Femenino En Las Claseunclassified
“…El clima de la clase, por tanto, juega un importante rol en el refuerzo de las diferencias de género presentes en las actitudes de logro, creencias y rendimientos del alumno (Lirgg, 1993). Con todo ello, parece evidente que entre los elementos que debería analizar el marco de investigación sobre la igualdad de trato se encuentran los aspectos metodológicos.…”
Section: Estudios Sobre Discriminación Del Sexo Femenino En Las Claseunclassified